علامة نائب الفاعل في القرآن الكريم في جزء 30 و تحليلها - Muhammad Jabir; Masyitah Nur Rahmi (Albariq: Jurnal Pendidikan Bahasa Arab, 2021)
This thesis is a literature study, and the objectives of this study are: to find out the types of subject replacement in chapter 30, and to find out the cause of the deletion of the subject. The method used in this scientific research is desk research. The method of data collection in this research is the method of identifying the verses of the Qur'an that have a substitute subject in it, which is contained in chapter 30, and then analyzing the substitute for the subject in the participle. using grammar rules related to subject substitution, commentaries and books related to subject participles. The results of the analysis show that there are 63 substitute subjects in chapter 30. It is divided into 4 parts. First substitute the obvious subject; second, substitute subject in the form of isim dhamir; third, substitute for the subject in the form of number;, fourth, substitute for the subject in the form of isim maushul. And also found the cause of the aborted subject, namely because it is common place; and ignorance of the subject.